The Economics of Bargaining Rights in the Fisheries of Nova Scotia and Atlantic Canada - Steinberg, Charles (Relations industrielles / Industrial Relations, 1975)
This paper contends that the legal precedents which have until so recently discouraged positive Canadian legislation, and which could still invalidate fresh legislative efforts, are based on an outdated view of the economic relations of fishermen and fish buyers. The following briefly examines the economic underpinnings of the Canadian fishermen's right to bar gain, with special reference to Nova Scotia and Atlantic Canada.